2019
DOI: 10.1590/0102-311x00014319
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from oral and oropharyngeal cancer in Brazil: impact of the National Oral Health Policy

Abstract: The objective was to investigate if there is an association between the mortality rates due to oral and oropharyngeal cancer in Brazil and the expansion of access to public primary and specialized dental care services that resulted from the implementation of the National Oral Health Policy, between 2000 and 2013. The mortality data were obtained from the records of the Mortality Information System and the exposure variables were obtained from databases of the Brazilian Ministry of Health and the Brazilian Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 42 publications
2
50
0
14
Order By: Relevance
“…The lower coverage of oral health in primary care and the absence of DSC are related to the higher risk of hospitalization for oral cancer, according to the ndings of this investigation. Studies have also found similar impacts of these variables on oral cancer mortality rates in Brazil in recent decades 13,15 . The lack of access to health services is one of the main factors related to the delay in the diagnosis of oral cancer, which often results in the need for more aggressive and mutilating treatments, reducing the individual's survival 25 .…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The lower coverage of oral health in primary care and the absence of DSC are related to the higher risk of hospitalization for oral cancer, according to the ndings of this investigation. Studies have also found similar impacts of these variables on oral cancer mortality rates in Brazil in recent decades 13,15 . The lack of access to health services is one of the main factors related to the delay in the diagnosis of oral cancer, which often results in the need for more aggressive and mutilating treatments, reducing the individual's survival 25 .…”
Section: Discussionmentioning
confidence: 67%
“…Socioeconomically disadvantaged individuals are often diagnosed with lesions in advanced clinical stages and with cervical metastases, which require complex treatments performed in the hospital setting 8 . Previous studies that used regions and states as sample units found no association between the Gini coe cient and oral cancer rates 13,15 . However, other studies with more speci c and similar populations, considering cities and neighborhoods, were able to detect a positive association between income inequality and oral cancer, like the present study 20,21 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Studies have found that specific health-related factors are regarded as risks after adjustment for common risk factors. An investigation was performed within specific health-related factors, including nutrition [28,29], oral health [30][31][32][33][34][35][36][37][38], and physical performance [39][40][41][42][43][44][45]. In addition to this risk evaluation, a comprehensive assessment for the risk factors for mortality is necessary for planning health promotion for older adults [46,47], decision of priority of intervention [48][49][50], and health-related political decision-making.…”
Section: Introductionmentioning
confidence: 99%